Improving Students’ Creative Thinking Skills through the IBSC (Investigation Based Scientific Collaborative) Learning Model Based on E-Learning - Ifa Lutfiah; Peni Suharti; Asy'ari Asy'ari (SEJ (Science Education Journal), 2021)
This research was aimed to describe (1) the implementation; (2) students' creative thinking skills; (3) students' cognitive learning outcomes; (4) student responses in the implementation of the IBSC (Investigation Based Scientific Collaborative) learning model based on e-learning. This is a pre-experimental study with One-Group Pre-test-Post-test Design. The sample in this study were students of class XI MIPA 2 SMA Walisongo Gempol. Data were collected through tests, observations, and questionnaires with creative thinking skills test instruments, observation sheets on the implementation of IBSC (Investigation Based Scientific Collaborative) learning model, fluency indicator observation sheets, and student response questionnaires to the IBSC (Investigation Based Scientific Collaborative) model. The data are analyzed descriptively and statistically through the Wilcoxon test with α = 0.05. The conclusions from the research are (1) the implementation of the IBSC (Investigation Based Scientific Collaborative) learning model based on e-learning to improve the creative thinking skills of class XI MIPA2 students is categorized as very good; (2) students' creative thinking skills in e-learning-based IBSC (Investigation Based Scientific Collaborative) learning have increased; (3) students' cognitive learning outcomes in e-learning-based IBSC (Investigation Based Scientific Collaborative) learning are complete; (4) student response to the IBSC (Investigation Based Scientific Collaborative) learning model based on e-learning is positive.